1996
DOI: 10.1177/004728759603400302
|View full text |Cite
|
Sign up to set email alerts
|

Megaresort on My Doorstep: Local Resident Attitudes toward Foxwoods Casino and Casino Gambling on Nearby Indian Reservation Land

Abstract: Residents of three rural communities in southeastern Connecticut, adjacent to the Native American-owned Foxwoods Resort and Casino, have mixed reactions to the casino and their Native American neighbors. Three years of surveys are used to monitor changing attitudes, analyze and model current attitudes, and predict acceptance offuture development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 23 publications
4
68
0
Order By: Relevance
“…Those respondents who displayed higher levels of satisfaction with the environment usually held more positive attitudes toward casinos. Similar findings were reported by Perdue et al (1995) in South Dakota and Colorado, as well as by Carmichael et al (1996) in the Foxwoods Tribe.…”
Section: Environmental Impactssupporting
confidence: 87%
See 2 more Smart Citations
“…Those respondents who displayed higher levels of satisfaction with the environment usually held more positive attitudes toward casinos. Similar findings were reported by Perdue et al (1995) in South Dakota and Colorado, as well as by Carmichael et al (1996) in the Foxwoods Tribe.…”
Section: Environmental Impactssupporting
confidence: 87%
“…Garrett (2004) also observed that casino operations do not promise to create local employment if they are established in rural or developing areas, where the workforces may be relatively unskilled, because these casinos are more likely to hire more skilled labor from outside instead of preferentially employing locals. A few studies have even indicated that the opening of a casino did not lead to any improvement or have any positive impact on recreation options (Carmichael et al, 1996;Long, 1996).…”
Section: Economic Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall quality of life was measured with 6 items (Diener et al, 1985;Sirgy, 2002) Three questions were asked to measure residents' support for further tourism development. Residents were asked to indicate their level of agreement with the statements related to their support for further tourism development (Allen et al, 1993;Carmichael, Peppard, & Boudreau, 1996). Table 2 shows the correlation coefficient between those five constructs.…”
Section: Measurement Scalesmentioning
confidence: 99%
“…Sirakaya, Teye and Sonmez (2002) state that, as Doxey's (1975) Irridex and Butler's (1980) Destination Life Cycle Model suggest, local people's attitudes towards tourism keep changing throughout various stages of tourism development; hence, an investigation of local communities' attitudes is important for community development. Local people's attitudes towards tourism are also vital for themselves, because they have few opportunities to express their opinions in the decision-making process (Carmichael, Peppard, & Boudreau, 1996). Andereck and Vogt (2000) consider that this importance is derived from the fact that it is the local people who ultimately decide which changes brought about by tourism are acceptable and which are not.…”
Section: Tourism Impact and Local Communities' Views Of Changes Causementioning
confidence: 99%